2016
DOI: 10.1038/oncsis.2016.68
|View full text |Cite
|
Sign up to set email alerts
|

FOXK1 interaction with FHL2 promotes proliferation, invasion and metastasis in colorectal cancer

Abstract: The transcriptional factor Forkhead box k1 (FOXK1) is a member of the FOX family. The abnormal expression of FOXK1 may have an important role in tumour development. Our previous studies showed that four-and-a-half LIM protein 2 (FHL2) is a critical inducer of the epithelial-to-mesenchymal transition (EMT) and invasion. However, the molecular mechanism by which FOXK1 synergizes with FHL2 tumour proliferation, EMT and metastasis is not well defined. We evaluated that messenger RNA (mRNA) and protein expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 35 publications
6
46
0
Order By: Relevance
“…CCK-8 and Transwell assays, demonstrated that restoration of FOXK1 significantly abrogated the effects of LINC01503 knockdown on CRC cell proliferation and invasion, which suggested that FOXK1 has an oncogenic role in CRC. This result was consistent with that of a previous study on FOXK1 (25). Therefore, these results demonstrated that LINC01503 promotes CRC progression via enhancing the expression of FOXK1.…”
Section: Discussionsupporting
confidence: 93%
“…CCK-8 and Transwell assays, demonstrated that restoration of FOXK1 significantly abrogated the effects of LINC01503 knockdown on CRC cell proliferation and invasion, which suggested that FOXK1 has an oncogenic role in CRC. This result was consistent with that of a previous study on FOXK1 (25). Therefore, these results demonstrated that LINC01503 promotes CRC progression via enhancing the expression of FOXK1.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, FOXK1 knockdown in Snail-overexpressing cells led to EMT reversion (Fig. 2B).Some reports have shown actin cytoskeleton regulation of the EMT in metastatic cancer cells [12,26]. Thus, we stained F-actin with phalloidin, followed by immunofluorescence analysis, which showed that Snail-overexpressing cells had an elongated cellular morphology and the presence of F-actin fibers compared with vector cells, a hallmark of the mesenchymal phenotype.…”
Section: Snail-foxk1 Axis Promotes Emt-mediated Crc Cells Invasion Anmentioning
confidence: 76%
“…FOXK1 is a proto-oncoprotein that is overexpressed in various cancer types [31][32][33]. Ectopic expression of FOXK1 markedly enhances cell proliferation, migration, and invasion in gastrointestinal cancer cells [15,26]. We recently demonstrated that FOXK1 induces EMT progression and predicts poor prognosis in human gastric cancer [15,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous reports have demonstrated, FOXK1 promotes cell proliferation in prostate cancer (39), colorectal cancer (40) and gastric cancer (41). In order to investigate whether the enhancing effect of FOXK1 on cell proliferation is caused by inhibition of apoptosis or promotion of the cell cycle, cell apoptosis was assessed after FOXK1 was silenced; however, no significant effect was observed.…”
Section: Discussionmentioning
confidence: 99%